METAMORPHISM TODAY: NEW SCIENCE, OLD PROBLEMS - Touret J.L.R.; Nijland T.G. (My University, 2002)
A concise history of the discipline of metamorphic petrology is presented, from the eighteenth-century concepts of Werner and Hutton to the end of the twentieth century.